Book Review: JANEWAY, William H.; Doing Capitalism in the Innovation Economy: Markets, Speculation and the State; Cambridge University Press, New York, United States of America; 2012; 329 p.; ISBN 978-1-107-03125-8 - Malafaia, Thiago Corrêa (Mural Internacional, 2014)
Esta resenha refere-se ao livro de 2012 de William H. Janeway: "Doing Capitalism in the Innovation Economy: Markets, Speculation and the State". É, de fato, uma surpreendente contribuição ao debate, tratando temas como se crises são desejáveis, bem como o papel do Estado quanto ao tema. O autor combina visões prática e teórica no tratamento da matéria. De acordo com ele, o Estado deveria fomentar pesquisas tanto na base da cadeia produtiva quanto em seu final de forma constante, não apenas quando há falhas de mercado. Não fazê-lo pode ter consequências. Por um lado, no curto prazo, pode-se esperar que aumentos no crescimento, emprego e renda; no longo prazo, por outro lado, pode-se também esperar a perda da liderança da "Economia de Inovação". ABASTRACT This book review covers William H. Janeway's 2012 book "Doing Capitalism in the Innovation Economy: Markets, Speculation and the State". It is, indeed an astonishing contribution to the debate, dealing with the desirability of economic crisis, the interrelations between economic crisis and innovation and also the role of the state in the matter. The author combines a practitioner's view and an academic's view to this issue. After him, the state should help fund Upstream and Downstream research permanently, not only at market failure times affirming that not doing so could have consequences. In the one hand, on the short run, one can expect to experience improvements in growth, employment and income, on the long run, however, one can also expect to loose the leadership of the “Innovation Economy”. Palavras-chave: resenha, capitalismo, economia de inovação Keywords: book review, capitalism, innovation economy DOI 10.12957/rmi.2014.10979 Recebido em 10 de maio de 2014 / Received on May 10, 2014 . Aceito em 22 de maio de 2014 / Accepted on May 22, 2014